Evaluation of the Use of Anti-Diabetic Drugs in Outpatient Type 2 Diabetes Mellitus Patients at Lasinrang Regional General Hospital, Pinrang Regency in 2023 - Nur Azizah, Rizqi; Damayanti, Alfina; Yuliana, Dewi (B-CRETA Publisher (CV. Borneo Citra Kreatama), 2024)
Diabetes Mellitus (DM), including a disease in the form of metabolic disorders characterized by impaired insulin secretion, impaired insulin production and insulin sensitivity, causing an increase in blood sugar levels (hyperglycemia). This study aims to determine the use of antidiabetic drugs which include the right drug, the right dose, the right indication and the right frequency of administration in outpatient type II diabetes mellitus patients at Lasinrang Regional General Hospital, Pinrang District in 2023. This study is a non-experimental research with a descriptive design retrospectively. The sample in this study is all outpatients with a diagnosis of type II diabetes mellitus at the Lasinrang Regional General Hospital, Pinrang District in 2023. The sampling technique used is purposive sampling. The sample of this study is medical record data of patients with type II diabetes mellitus in 2023, which is adjusted to the inclusion criteria. The results of the study showed that of 87 samples consisting of 55 women and 32 men, all of which met the inclusion and exclusion criteria, and showed that the prevalence of age was more susceptible to be affected at the age of 46-55 years as many as 40 patients (45.98%). In the analysis of the accuracy of drug use, outpatient type II diabetes mellitus patients at the Lasinrang Regional General Hospital, Pinrang regency in 2023 have an indication accuracy of 100%, 100% drug accuracy, 100% dose accuracy, and 100% accuracy frequency of drug administration.